1999
DOI: 10.1006/viro.1999.9736
|View full text |Cite
|
Sign up to set email alerts
|

The Dileucine-Based Sorting Motif in HIV-1 Nef Is Not Required for Down-Regulation of Class I MHC

Abstract: A dileucine-based protein sorting motif has recently been identified within the C-terminal, solvent-exposed loop of HIV-1 Nef and has been shown to be required for Nef-mediated down-regulation of CD4 and for optimal viral infectivity. Here, we report that mutation of the dileucine motif has no effect on Nef-mediated down-regulation of class I MHC heavy chain. Instead, deletion of an acidic domain just N-terminal of the polyproline helix of the SH3-binding domain significantly impairs this function. These data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
24
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(29 citation statements)
references
References 20 publications
5
24
0
Order By: Relevance
“…2C and D). A partial effect of mutating the acidic domain and the first polyproline domain of Nef is consistent with prior reports (21,25,32). All of these mutants, except D 123 G, were active at CD4 downmodulation ( Fig.…”
supporting
confidence: 92%
“…2C and D). A partial effect of mutating the acidic domain and the first polyproline domain of Nef is consistent with prior reports (21,25,32). All of these mutants, except D 123 G, were active at CD4 downmodulation ( Fig.…”
supporting
confidence: 92%
“…It has also been reported that the recognition of tyrosine-based endocytotic signals clearly involves a dimeric 2 chain of the clathrin adapter AP2 complex (49).…”
Section: Discussionmentioning
confidence: 97%
“…the possibility that the pathways used for downmodulation of CD4 and class I MHC by LAT-Nef and Nef are different. To examine this, we utilized a series of well-characterized mutations in Nef that previously had been shown to differentially affect the two pathways (51,54). The mutations chosen were D123G, previously shown to inhibit both CD4 and class I MHC downmodulation (39); L164, L165/AA (LL/AA), previously shown inhibit only CD4 downmodulation (7,29); and E62, E63, E64, and E65/AAAA (EEEE/AAAA), previously shown to inhibit only class I MHC downmodulation (31).…”
Section: Vol 78 2004 Lipid Raft Targeting and Nef Function 1689mentioning
confidence: 99%